Risk perception of behavioural adaptation recommendations towards COVID-19 and its related factors in Indonesia - Siswati, Tri; Benita, Stella; Paramita, Iswari; Susilo, Joko; Waris, Lukman; Paramashanti, Bunga A. (International Journal Of Community Medicine And Public Health, 2021)
Background: The number of coronavirus disease 2019 (COVID-19) cases in Indonesia keeps increasing even though the Indonesian government continuously communicates mitigation strategies. This study aimed to- estimate the proportion of risk perception towards COVID-19 behavioural adaptation recommendations and examine its sociodemographic determinants in Indonesia. Methods: An online-based cross-sectional study was conducted among 1,007 individuals aged 15-60 years old. Our primary outcome was risk perception towards COVID-19 behavioural adaptations. Independent variables included sociodemographic factors such as sex, age, educational level, type of occupation, family size, economic status, and regions. Descriptive statistics, univariate logistic regression, and multiple logistic regression were performed to analyse the data. Results: Around 78% of participants had a high level of risk perception related to COVID-19 behavioural adaptation recommendations. Among the participants, being females (AOR= 2.40; 95% CI: 1.76-3.27) and health professionals (AOR= 1.42; 95% CI: 0.64-1.44) were significantly associated with higher risk perceptions. In contrast, residing in Kalimantan and Sulawesi (AOR= 0.43; 95% CI: 0.23-0.79) and Eastern Indonesia (AOR= 0.43; 95% CI: 0.21-0.88) were significantly associated with lower risk perceptions. Conclusions: Despite the high levels of risk perceptions among the Indonesian population, sociodemographic variations drove the risk perception of behavioural adaptation recommendations concerning COVID-19.